2017
DOI: 10.1002/2017gl074553
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic pollution elevates the peak height of new particle formation from planetary boundary layer to lower free troposphere

Abstract: New particle formation (NPF) and subsequent growth are primary sources of atmospheric aerosol particles and cloud condensation nuclei. Previous studies have been conducted in relatively clean environments; investigation of NPF events over highly polluted megacities is still lacking. Here we show, based on a recent yearlong aircraft campaign conducted over Beijing, China, from April 2011 to June 2012, that NPF occurrence peaks in the lower free troposphere (LT), instead of planetary boundary layer (PBL), as mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 60 publications
(80 reference statements)
0
17
0
Order By: Relevance
“…Airborne observations suggest that in some regions NPF and subsequent particle growth seem to be confined into the BL (O'Dowd et al , Crumeyrolle et al 2010, while in other regions this phenomenon may also take place in the FT (Rose et al 2015a, Bianchi et al 2016, Berland et al 2017 or at the interface between the BL and FT (Siebert et al 2004, Dadashazar et al 2018. In Beijing, China, the height in the atmosphere having the strongest NPF was observed to move from within the BL at low aerosol loadings to the top of the BL or to the lower FT at high aerosol loadings (Quan et al 2017). Observations in several mountain-top locations indicate a relatively frequent occurrence of seemingly regional NPF events at high altitudes (see section 3.2.5).…”
Section: Spatial Characteristicsmentioning
confidence: 99%
“…Airborne observations suggest that in some regions NPF and subsequent particle growth seem to be confined into the BL (O'Dowd et al , Crumeyrolle et al 2010, while in other regions this phenomenon may also take place in the FT (Rose et al 2015a, Bianchi et al 2016, Berland et al 2017 or at the interface between the BL and FT (Siebert et al 2004, Dadashazar et al 2018. In Beijing, China, the height in the atmosphere having the strongest NPF was observed to move from within the BL at low aerosol loadings to the top of the BL or to the lower FT at high aerosol loadings (Quan et al 2017). Observations in several mountain-top locations indicate a relatively frequent occurrence of seemingly regional NPF events at high altitudes (see section 3.2.5).…”
Section: Spatial Characteristicsmentioning
confidence: 99%
“…Clarke et al (1998) observed nucleation in cloud outflow regions when SA concentrations approached or dropped below ∼ 5-10 µm 2 cm −3 . However, recent work shows that increased aerosol loadings suppress nucleation in the boundary layer but enhance it in the lower FT owing to a chain of aerosol-radiation-photochemistry interactions (Quan et al, 2017). Nucleation events in Birmingham, United Kingdom, occurred for SA concentrations up to 300 µm 2 cm −3 , but with most events below 100 µm 2 cm −3 (Alam et al, 2003).…”
Section: Nucleation In the Eilmentioning
confidence: 99%
“…As underscored by Kumula's protocol [10], sensitive differential mobility analyzers and mass spectrometers are required to evaluate the number and the nanometer size of the newly-formed particles. As a result, field observations of NPF in free troposphere are rather scarce and restricted to only a few mountain locations [16] or to very interesting but sporadic airplane field campaigns [23], which can hardly provide the spatial and temporal extent of nucleation [24], due to their intrinsics limit duration.…”
Section: Introductionmentioning
confidence: 99%